Estimating the cost to government of providing undergraduate and postgraduate education - Jack Britton; Claire Crawford (Institute for Fiscal Studies (IFS), 2015)
The uncertainty over future student loan repayments means that the debate about whether the government contribution to the cost of higher education is too high will almost certainly continue. However, as our analysis makes clear, whatever the current estimate of the RAB charge, it is based on a large number of assumptions, many of which are likely to change in future (e.g. the rate of graduate earnings growth). It also depends hugely on the way in which we value expected future repayments in the present. It would thus be a mistake to undertake reforms solely on the basis of a single uncertain figure. The loan subsidy is just one part of a package of support that the government offers to students and universities which must be taken into consideration when deciding on the extent to which it wishes to subsidise higher education in England.
Keywords: 330